Profil Fisika-Kimia Minyak Feun Kase (Thevetia Peruviana) Sebagai Sumber Baru Energi Terbarukan - Jefry Presson; Yohana Ivana Kedang; Suwari Suwari (Fakultas Pertanian, Universitas Timor, 2021)
The depletion of world fossil energy has led to the development of renewable energy from vegetable oils, including Feun Kase with abundant vegetable oils. The main focus of this research was to identify the physicochemical properties and to explore the potential of Indonesian Feun Kase (Thevetia peruviana) oil as renewable energy. Feun Kase oil has been isolated by press and soxhlet method. The soxhlet (66.32% weight) provided a higher yield than the press (25.58% weight). The oil yielded was directly tested for the physicochemical test according to SNI 7182: 2015 (Indonesian National Standard). The parameters in this research were water content, acid number, saponification number, iodine value, density, viscosity, cetane number, flash point, and cloud point. The GCMS profile showed the presence of several fatty acids such as hexadecenoic acid (palmitic acid), 9,12−octadecadienoic acid (linoleic acid), 9−octadecenoic acid (oleic acid), and octadecenoic acid (stearic acid). Although there was no conclusion in terms of biodiesel, this research could give the report as the basic information that revealed the potential of Feun Kase oil. Several tests revealed that Feun Kase oil can be used as the feedstock for biodiesel. Unlike palm oil, the non-edible oil of Feun Kase does not compete with the food sector. Thus, it indicated that Feun Kase oil is a very competitive feedstock for renewable energy.